Psicología de la mujer - Miyashiro Bueno, Camila Alejandra (2020)
This state of the art seeks to provide current and relevant information regarding the latest research with respect to an important part of the Psychology of Women—gender stereotypes—and its influence on different areas of women’s lives, such as family life, education, and work. To this end, different theories, national and international empirical studies, and models of prevention and intervention were reviewed. In this line, it was found that gender stereotypes contribute to significant gender inequality, with women being at disadvantage in comparison to men, especially in regard to professional development, choosing an academic major, experiences of violence, among others. In light of these findings, it becomes important to implement, disseminate, and research models of prevention that not only allow for the eradication of gender stereotypes, but prevent their onset to begin with, in order to facilitate greater equality. Recommendations include collaborative work, across psychologists and other social science professionals, to create interventions in educational institutions, families, and other relevant environments to reduce the impact of gender stereotypes in a holistic manner.